Which factors can affect the productivity and dynamics of cod stocks in the Baltic Sea, Kattegat and Skagerrak?. (15th May 2022) - Bryhn, Andreas C.; Bergek, Sara; Bergström, Ulf; Casini, Michele; Dahlgren, Elin; Ek, Caroline; Hjelm, Joakim; Königson, Sara; Ljungberg, Peter; Lundström, Karl; Lunneryd, Sven Gunnar; Ovegård, Maria; et al.
Abstract: Stocks of Atlantic cod ( Gadus morhua ) in the Baltic Sea, Kattegat and Skagerrak (N. Europe) have been strongly exploited for decades bringing them into an enduringly depleted status. Scientific cod stock related advice for targeted and mixed fisheries is provided on an annual basis by the International Council for Exploration of the Sea. This advice forms a basis for ministerial decisions on, e.g., the total allowable catch and management plans. Despite measures to reduce fishing-induced mortality of cod, such as catch and effort restrictions, increased gear selectivity, closed areas and seasons, clear signs of recovery are yet to be seen. Thus, traditional advice for the management of these stocks may have to be complemented by advice on supporting measures focusing on other pressures hampering the recovery of cod. The present study elaborates on potential supportive measures for cod stock recovery in the Baltic Sea, Kattegat, and Skagerrak (including local populations where applicable), based on current knowledge. The list of measures presented here is the outcome of in-depth discussions on the state-of-the-art knowledge, among cod experts and further with stakeholders with the aim to follow principles of ecosystem-based fisheries management. Following the identification of different pressures on and prerequisites for the separate stocks, the listed measures differ between stocks and include cod bycatch mortality reduction, alterations in fisheries affecting food sources for cod, restocking, protection of juvenile habitats, and reduced predation. The literature review and the list of measures are intended to provide decision-support for managers and policymakers aiming to provide conditions for the cod stocks to recover. Graphical abstract: Image 1